Understanding and managing patients with overlapping disorders of gut–brain interaction. (April 2023) - Balsiger, Lukas Michaja; Carbone, Florencia; Raymenants, Karlien; Scarpellini, Emidio; Tack, Jan
Summary: Disorders of gut–brain interaction (DGBI) are frequently encountered in clinical practice, and recommendations for diagnosis and management are well established. In a large subset of patients, more than one DGBI diagnosis is present. This group of patients with more than one DGBI diagnosis have higher symptom severity and impact than patients with only one DGBI diagnosis, and the management approach is not well established for those with overlapping diagnoses. This Review aims to guide clinicians to understand, recognise, and manage overlapping DGBI by identifying causes and pitfalls of overlap conditions, and presenting potential practical approaches to diagnosis, treatment, and follow-up. Several clinical factors can contribute to finding overlapping DGBI, including the anatomical basis of the Rome diagnostic criteria, the potential confusion of symptom descriptors, and patients' biases towards higher symptom intensity ratings. Overlapping DGBI could also be caused by mechanistic factors such as pathophysiological mechanisms involving multiple gastrointestinal segments, and the effect of disorders in one segment on sensorimotor function in remote gastrointestinal parts, through neural or hormonal signalling. Key initial steps in the management of overlapping DGBI are detailed history taking, which can be facilitated using pictograms; carefully assessing the relative timing and cohesion of different symptoms; and recognising associated psychosocial dysfunction. Unnecessary technical investigations and complex combination treatment schedules should be avoided. Based on the identification of the dominant symptom pattern and putative underlying pathophysiological mechanisms, a single treatment modality should preferably be initiated, considering the efficacy spectrum of different therapies. Follow-up of the patient's condition allows the therapeutic approach to be adjusted as needed, while avoiding unnecessary additional technical investigations.